S100A8/A9 high-expression macrophages mediate renal tubular epithelial cell damage in acute kidney injury following acute type A aortic dissection surgery - Cai, Xiujuan; Li, Xin; Shi, Jian; Tang, Lu; Yang, Jie; Yu, Ronghuang; Wang, Zhigang; Wang, Dongjin (Frontiers in Molecular Biosciences, 2025)
BackgroundAcute kidney injury (AKI) is a major complication after acute type A aortic dissection (ATAAD), with an incidence rate of 20–66.7%. Many patients with AKI after ATAAD surgery show no clear signs of ischemia-reperfusion injury. In our previous study, S100A8 and S100A9 were identified as predictive biomarkers of AKI after ATAAD surgery. These proteins are primarily expressed in neutrophils and macrophages, where they contribute to cell damage and immune cell activation. However, the roles of S100A8/A9 in ATAAD-associated AKI remain unclear.MethodsIn this study, transcriptomics sequence was applied to identify differentially expressed genes in renal tubular epithelial cells (TCMK-1), stimulated by culture supernatant of S100A8/A9 overexpressed and downregulated RAW264.7 cells. Single-cell sequencing data were used to identify cell clusters with high S100A8/A9 expression. Cross-analysis between RNA sequencing datasets was used to investigate common pathways enrichment in both in vitro and in vivo models. Molecular biology experiments were used to explore the downstream signaling pathways of S100A8/S100A9.ResultsWe found that S100A8/S100A9 expression levels were increased and co-localized primarily with macrophages in the kidneys of AKI mice. Marker genes of M1-type macrophages, like Nos2 and Il1b, were upregulated in S100A8/A9 overexpressed M1-type macrophages, while the opposite was observed in the downregulated group. In transcription sequencing results, TCMK-1 cells stimulated by the supernatant from S100A8/A9 overexpressed and downregulated RAW264.7 cells can activate the TNF and PPAR pathway respectively. Cross-analysis revealed that the TNF signaling, IL-17 signaling, and other inflammatory pathways were enriched in both S100A8/A9-related renal tubular epithelial cell impairment and other AKI sequencing datasets. Finally, recombinant protein S100A8/A9 activated the TNF signaling pathway in renal tubular epithelial cells.ConclusionThese findings suggested that S100A8/A9 were promising predictive biomarkers for AKI after surgery for ATAAD. S100A8/A9 were upregulated and primarily localized in renal macrophages, where they promoted the transformation of macrophages into the M1 phenotype. S100A8/A9 overexpressed macrophages activated the TNF signaling pathway through secretion and direct interaction with renal tubular epithelial cells, highlighting the critical role of TNF signaling in AKI after ATAAD surgery.